Large Ring Cyclodextrin and Cosolvency-based Techniques to Improve Solubility of Antifungal Drug (Asian Journal of Pharmaceutics (AJP), 2023)
Objective: Posaconazole is used to treat oral candidiasis in patients who are severely immunocompromised.Posaconazole is categorized under BCS Class-Ⅱ drug, i.e., low solubility and high permeability. Posaconazolehas very poor water solubility. The current study aimed to improve water solubility of posaconazole usingdifferent approaches. Materials and Methods: To enhance the solubility of drug, two methods, inclusioncomplex and cosolvency approach, were performed. In inclusion complex method, beta-cyclodextrin (β-CD)and hydroxypropyl β-CD (HP-β-CD) were used for the preparation of inclusion complex. In cosolvency method,two different solvents polyethylene glycol-400 (PEG-400) and propylene glycol (PG) were used. Results: Theinclusion complex of HP-β-CD was prepared by physical mixing, kneading, and solvent evaporation methodsby taking 1:0.5, 1:1, and 1:2 molar ratio of Drug: HP-β-CD. From the results of dissolution study of complex, itwas observed that there was no significant improvement in solubility of drug. In cosolvency approach, maximumsolubility of drug was found in a ratio of 0:100% v/v for both solvents. The solubility of drug in Water: PEG- 400and Water: PG solvents were found to be 20.228 ± 0.0169 mg/mL and 17.204 ± 0.0178 mg/mL, respectively.Conclusion: In cosolvency method, it was observed that drug has more solubility in PEG- 400 compared to PG.Hence, PEG-400 solvent was selected for drug solubilization.